2000
DOI: 10.3923/pjbs.2000.2256.2259
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Different Wheat CuRivers (Flour) Against the Attack of Tribolium castaneum Herbst (Coleoptera: Tenebrionidae) Under Laboratory Conditions

Abstract: It was concluded that keeping Chakwal 86 as (susceptible/ check), Sariab 92 and Bakhtawar were found to be highly susceptible. Inqilab 91, Khyber 87, Faisalabad 85 were not significantly different from the standard Chakwal 86. Rawal 87 and Pak 81 turned out to be partially resistant. C591 turned out to be susceptible to partially resistant against Red FlourBeetle (RFB). The results showed that there was variability in different wheat cultivars and none of them found to be completely resistant. Although complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Similarly, Khattak et al (2000) reported that the attack of pest reduces the protein, ash, fiber and fats from the stored grains. Various experiments concerning performance of wheat genotypes has been conducted in Pakistan by Saima and Muhammad (2000), Ali et al (2009) and Sarwar et al (2012Sarwar et al ( , 2013 observed that variability in various wheat varieties which turned out to be resistant or vulnerable against store grain pests. Mebarkia et al (2010) reported that lower resistance genotypes to various stored grain pests to grain pest attacks may be recognized low and high content of carbohydrate and protein.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Khattak et al (2000) reported that the attack of pest reduces the protein, ash, fiber and fats from the stored grains. Various experiments concerning performance of wheat genotypes has been conducted in Pakistan by Saima and Muhammad (2000), Ali et al (2009) and Sarwar et al (2012Sarwar et al ( , 2013 observed that variability in various wheat varieties which turned out to be resistant or vulnerable against store grain pests. Mebarkia et al (2010) reported that lower resistance genotypes to various stored grain pests to grain pest attacks may be recognized low and high content of carbohydrate and protein.…”
Section: Resultsmentioning
confidence: 99%